2003
DOI: 10.2109/jcersj.111.323
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Proton Conductivity of AlH2P3O10 nH2O under Various Water Vapor Pressures

Abstract: íXmOöC³ºjIP AlH 2 P 3 O 10 E nH 2 O mÀè«gÓéÄï`±Á« cDÀEìcE{R åw ¶YZp¤C1538505 sÚaeîê 461Stability and proton conductivity of AlH 2 P 3 O 10 EnH 2 O (n23) were investigated in the temperature range from 75 C to 150 C under various water vapor pressures. The hydrolysis from AlH 2 P 3 O 10 EnH 2 O to Al(H 2 PO 4 ) 3 started at 100 C under a relative humidity (RH) of 60÷, and further hydrolysis to AlPO 4 took place with increasing temperature and humidity. At 75 C, the original phase was maintained under saturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Similarly, it has been reported that AlH 2 P 3 O 10 ·nH 2 O has only one semicircle (C~4.58×10 − 11 F/cm) corresponding to bulk response at 75°C in 60% RH and only a 'spike' like response in 94% RH. This was explained by the increased surface conduction at high relative humidity since the total resistance decreases more than one order of magnitude after increase relative humidity from 60% to 94%RH [33]. It is almost certain that the conduction of Al(H 2 PO 4 ) 3 -H 3 PO 4 composites is dominated by protons as protons are the only ionic species that are likely to be mobile and there is no evidence to suggest electronic conduction from impedance measurements.…”
Section: Impedance Spectroscopy and Conductivitymentioning
confidence: 99%
“…Similarly, it has been reported that AlH 2 P 3 O 10 ·nH 2 O has only one semicircle (C~4.58×10 − 11 F/cm) corresponding to bulk response at 75°C in 60% RH and only a 'spike' like response in 94% RH. This was explained by the increased surface conduction at high relative humidity since the total resistance decreases more than one order of magnitude after increase relative humidity from 60% to 94%RH [33]. It is almost certain that the conduction of Al(H 2 PO 4 ) 3 -H 3 PO 4 composites is dominated by protons as protons are the only ionic species that are likely to be mobile and there is no evidence to suggest electronic conduction from impedance measurements.…”
Section: Impedance Spectroscopy and Conductivitymentioning
confidence: 99%
“…Isothermal desorption of water was measured at various external water-vapor pressures from 95% relative humidity (RH) to dry conditions (b 2% RH) at 130°C by using a pressure-resist thermogravimetric measurement system (Nihon Bell Co., Ltd.) in which the vapor pressure of water is controlled as previously described [30]. The RH was estimated by using the expression P H2O /P s where P H2O is the vapor pressure of water in the vessel and P s is the saturated water vapor pressure at 130°C.…”
Section: Characterization Of Membranesmentioning
confidence: 99%
“…x 2H 2 O were studied. Authors [8] showed that in vapor water above mentioned compound transfer first of all in Al(H 2 PO 4 ) 3 and then in AlPO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…For the reason the compounds are applied in different fields of technique. In papers [1,3,5,8] the series of materials with composition M III H 2 P 3 O 10 x 2H 2 O (where M III =Al, Ga, Fe, Mn, V, Cr), which have layer structure, is examined. Aluminum dihydrogen tripolyphosphate which belongs to these classes of materials is already used as a new non-toxic white anticorrosive pigment for painting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation